The effect of agile leadership on teachers' professional development and performance - Yalçın, Elif; Özgenel, Mustafa; Özgenel, Mustafa (Southern Connecticut State University, 2021)
The aim of the study is to determine the effect of the agile leadership characteristics of school principals on the professional development and performance of teachers. The relational survey model was used in the study and data were collected from 575 teachers. Data were collected through the Marmara Agile Leadership Scale, the Attitude Scale towards Professional Development and the Performance Scale. The data were analyzed by t-test, ANOVA, correlation, and regression tests. It was determined that the agile leadership characteristics of school principals perceived by teachers significantly predicted and positively affected teachers' attitudes towards professional development and their performances. In addition, it was revealed that teachers' attitudes towards professional development significantly predicted and positively affected their performance.
Keywords: Leadership; Agile leadership; Professional development; Teacher performance